2018
DOI: 10.2485/jhtb.27.213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-term Tumour Necrosis Factor-alpha (TNF-α) -stimulation on the Growth and Differentiation of MC3T3-E1 Osteoblast-like Cells

Abstract: Tumor necrosis factor-alpha (TNF-α) is an infl ammatory cytokine known to cause bone resorption, swelling and edema during tissue organization. Conversely, TNF-α has also been shown to participate in tissue regeneration during the wound healing process. We have previously investigated the eff ects of TNF-α on human dental pulp cell diff erentiation. Dental pulp cells are composed of diff erent cell types including primary odontoblasts and fi broblasts. We determined that the ratio of stem cells within the pulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several studies have reported that TNF-α inhibited Type I collagen production and ALP expression based on the blockage of osteoblast differentiation in osteoblastic clonal cell lines [33][34][35] . Furthermore, Inoue et al have shown that short-term stimulation by TNF-α delayed cell differentiation in osteoblast-like cells 36) . In this study of a heterogeneous BMSC population, it is not clear if there are different bone marrow subpopulations that acquire stem cell properties after TNF-α stimulation 37) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that TNF-α inhibited Type I collagen production and ALP expression based on the blockage of osteoblast differentiation in osteoblastic clonal cell lines [33][34][35] . Furthermore, Inoue et al have shown that short-term stimulation by TNF-α delayed cell differentiation in osteoblast-like cells 36) . In this study of a heterogeneous BMSC population, it is not clear if there are different bone marrow subpopulations that acquire stem cell properties after TNF-α stimulation 37) .…”
Section: Discussionmentioning
confidence: 99%
“…Rigid osseointegration at the implant-bone interface is the functional foundation of dental implants. Bone around dental implants is continuously remodeled, and various factors have been demonstrated to regulate this process, including local cytokines, growth factors and systemic hormones 1,2) .…”
Section: Introductionmentioning
confidence: 99%